ANALISIS PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGRAJIN GULA AREN DI KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Novia Fitri Yanti Saragih; Suharno Suharno; Harianto Harianto (Forum Agribisnis, 2018)
Palm sugar as a source of income is mostly produced by palm sugar producers who are in the village, depending on the population of existing palm trees. Available raw materials and prevailing prices affect income. This study aims to (1) analyze the structure of production costs and business income of palm sugar and (2) analyze the factors that influence the income of palm sugar producers in Rejang Lebong Regency, Bengkulu Province. The method used to analyze the cost structure is income analysis (π = TR - TC) by calculating the use of total costs (TC = TFC + TVC) used in once production process. Factors that influence palm sugar income are  price of palm sugar, number of productive trees, and yield of palm sugar. Primary data obtained from palm sugar prodicers using questionnaires and secondary data obtained from previous research. Analysis of factors that influence income using multiple linear regression analysis,  processed using the SPSS 16.0 Program. Research results show that the average income obtained by palm sugar craftsmen in Rejang Lebong District is Rp 150,374 / production. Palm sugar processing business is still feasible to be a business and profitable because the value of profitability obtained is 1.23. Factors that influence income significantly at the level of 95 percent in the form of prices and number of productive trees. Improvements in technological innovations and an increase in the population of palm sugar plants need to be improved to be able to increase the income of palm sugar’ producers in the Rejang Lebong Regency of Bengkulu Province.